Cultural Dynamics in The Evolution of Ibhea Obhea Dance in Doyo Lama Village, Papua: from Sacred Ritual to Secular Performance - Surya Peradantha, Ida Bagus Gede; Luh Kompyang, Sri Wahyuni (Institut Seni Indonesia Denpasar, 2025)
For the Doyo Lama community, the Ibhea Obhea dance is a cultural asset. This dance is at risk of extinction due to life's changing circumstances and regeneration stagnation. Cooperative initiatives are essential for the preservation and advancement of this dance. This study seeks to comprehend the transformation of Ibhea Obhea Dance and examine its effects on the dance's structure, function, and significance. This research employs a qualitative method with a socio-artistic approach to analyse alterations in the text and context of the Ibhea Obhea dance. We gathered data by observing the dance form with the elders of Doyo Lama village, conducting interviews about the history and significance of the Ibhea Obhea dance, reconstructing the dance, and documenting the artistic features of the dance. In collaboration with the elders, we reconstructed the dance by developing new vocal texts, synchronizing vocals with movements, and documenting the process through recordings of the reconstituted Ibhea Obhea dance. We conducted validation by correlating the video records with the traditional elders. The findings indicated that the modifications in this dance encompass the structural and artistic components. The community was aware of and approved of these changes. The Ibhea Obhea dance has evolved from a mystical rite into a ceremonial welcome for guests. This alteration enhances the significance of dancing by incorporating elements of hospitality, humanism, and cultural preservation. This study elucidates the impact of alterations in the boatbuilding tradition on the evolution of dance within a wider social and cultural framework.